A descriptive study on online health information-seeking behavior among adults attending a tertiary care hospital in central Kerala - Shaliet Rose Sebastian; V T Anjusha Joseph; Ann Elizabeth Sibichen (Wolters Kluwer Medknow Publications, 2023)
Background: The internet plays a crucial role in educating and empowering the health consumer, by providing a large quantity of information on health and health services at their convenience. Although people pay attention to the health information available online, they seldom remember the source of information or are mindful about the credibility of internet sites. As a consequence, online information can lead to patients being misinformed, a sense of distress, and an increase in the tendency toward self-diagnosis or self-treatment. Aim: This study aims to study the pattern of seeking online health information among adults attending a Tertiary Care Hospital in Central Kerala. Materials and Methods: A hospital-based cross-sectional study was conducted among 460 adults attending a tertiary care hospital in central Kerala. Results: Sixty-six percent of the study participants surfed the Internet to gather information about symptoms related to their condition. Forty-one percent of the study population preferred to discuss the information with their doctor. Majority of study subjects (58%) preferred better opportunities for doubt clearance with their consulting doctor instead of googling their symptoms. Conclusion: The present study recommends that online health information should be used in synergy with doctor-patient interactions which give them viable and true information to cope with their problems to disseminate the right knowledge in the community.